Diesel exhaust: current knowledge of adverse effects and underlying cellular mechanisms - Steiner, Sandro (Arch Toxicol, 2016)
Diesel engine emissions are among the most prevalent anthropogenic pollutants worldwide, and with the growing popularity of diesel-fueled engines in the private transportation sector, they are becoming increasingly widespread in densely populated urban regions. However, a large number of toxicological studies clearly show that diesel engine emissions profoundly affect human health. Thus the interest in the molecular and cellular mechanisms underlying these effects is large, especially concerning the nature of the components of diesel exhaust responsible for the effects and how they could be eliminated from the exhaust. This review describes the fundamental properties of diesel exhaust as well as the human respiratory tract and concludes that adverse health effects of diesel exhaust not only emerge from its chemical composition, but also from the interplay between its physical properties, the physiological and cellular properties, and function of the human respiratory tract. Furthermore, the primary molecular and cellular mechanisms triggered by diesel exhaust exposure, as well as the fundamentals of the methods for toxicological testing of diesel exhaust toxicity, are described. The key aspects of adverse effects induced by diesel exhaust exposure described herein will be important for regulators to support or ban certain technologies or to legitimate incentives for the development of promising new technologies such as catalytic diesel particle filters.